OPERATIONAL ANALYSIS TOOLS IN SOLVING TRANSPORT TASKS (Perner's Contacts, 2016)
The article describes the operational analysis as an essential tool for optimizing decision-making process. I focus on those parts of the operational analysis, which is used in transport and distribution, as well as a thriving company based transportation service processes. I cite an example calculation optimizing transport service customers using the tools of operational analysis.
Keywords: operational analysis; transportation; operation